Light-enabled resistive memory switching - Law, Madeline Su Ling (2016)
Non-volatile memory refers to memory devices that are able to retain data even when power supply is removed. Flash memory takes up majority of the non-volatile memory market. Planar Flash with NAND and NOR type, uses floating gate to store electrons. Vertically stacked or 3D Flash with charge trapping technology had since taken over planar Flash as planar Flash reaches a development-end due to scalability challenges. Unlike typical planar Flash memories, stacking of memory cells vertically in 3D Flash can massively increase storage capacity without compromising device’s reliability and performance. Next generation memory includes the Resistive Random Access Memory (RRAM), which is one of the most promising technology to replace Flash. RRAM stores data by changing its resistance states by the formation of nanoparticles filament due to electrical stress. It was proposed that electrical stress to the oxide causes oxygen ions of the oxide material to diffuse out to the surrounding, forming a local conductive filament. The formation of the conductive filament allows the local point of the oxide material to conduct temporarily. This process is reversible through a negative electrical stress, which disrupts the conductive filament, allowing the oxide to revert back its insulating properties. Oxides with larger bandgaps such as HfO2 and ZrO2 are found to be photon-responsive under white light illumination after electrical soft-breakdown (SBD). This behaviour, termed as “negative photoconductivity” can be defined as the disruption of the conductive filament when oxide is exposed to white light illumination due to the excitation of interstitial oxygen ions of the filament, causing them to recombined back into the filament.